An exploration of social participation for young adults following a first psychotic episode. Issue 1 (2nd January 2020) - Fox, Valerie
ABSTRACT: Individuals with mental illness continue to be among the most excluded in society. A thorough understanding of how social participation shifts for individuals following their first psychotic break is needed to develop interventions targeting social integration and participation. The objective of this collaborative ethnography was to explore social participation for young adults following first episode psychosis (FEP). The study adopted two specific aims: 1) explore perceived opportunities for participation for young adults following FEP; and 2) explore the sociocultural mechanisms that facilitate or hinder the experience of social participation for young adults following FEP. Semi-structured interviews, participant observations, and discourse elicitation were used for data collection. Five factors were revealed that impacted participants' social participation: 1) social norms and expectations; 2) sense of responsibility to others; 3) participants' occupational histories and relationships prior to the illness; 4) change in the environment; and 5) forms of participation available. These factors were not purely social; instead, social and individual factors transacted in a complex way to impact participants' experiences of belonging and their life trajectories following FEP. It is this relationship that must be the point of intervention. Occupation is the medium through which this relationship can be examined and addressed to promote social participation and belonging.